COVID‐19 in early 2023: Structure, replication mechanism, variants of SARS‐CoV‐2, diagnostic tests, and vaccine & drug development studies - Ilker Polatoğlu; Tulay Oncu‐Oner; Irem Dalman; Senanur Ozdogan (MedComm, 2023)
Abstract Coronavirus Disease‐19 (COVID‐19) is an infectious disease caused by severe acute respiratory syndrome‐coronaviruses‐2 (SARS‐CoV‐2), a highly pathogenic and transmissible coronavirus. Most cases of COVID‐19 have mild to moderate symptoms, including cough, fever, myalgias, and headache. On the other hand, this coronavirus can lead to severe complications and death in some cases. Therefore, vaccination is the most effective tool to prevent and eradicate COVID‐19 disease. Also, rapid and effective diagnostic tests are critical in identifying cases of COVID‐19. The COVID‐19 pandemic has a dynamic structure on the agenda and contains up‐to‐date developments. This article has comprehensively discussed the most up‐to‐date pandemic situation since it first appeared. For the first time, not only the structure, replication mechanism, and variants of SARS‐CoV‐2 (Alpha, Beta, Gamma, Omicron, Delta, Epsilon, Kappa, Mu, Eta, Zeta, Theta, lota, Lambda) but also all the details of the pandemic, such as how it came out, how it spread, current cases, what precautions should be taken, prevention strategies, the vaccines produced, the tests developed, and the drugs used are reviewed in every aspect. Herein, the comparison of diagnostic tests for SARS‐CoV‐2 in terms of procedure, accuracy, cost, and time has been presented. The mechanism, safety, efficacy, and effectiveness of COVID‐19 vaccines against SARS‐CoV‐2 variants have been evaluated. Drug studies, therapeutic targets, various immunomodulators, and antiviral molecules applied to patients with COVID‐19 have been reviewed.